The autoimmune conundrum in common variable immunodeficiency disorders. Issue 6 (December 2015) - van de Ven, Annick A.J.M.; Warnatz, Klaus
Abstract : Purpose of review: Autoimmune and inflammatory manifestations are the biggest clinical challenge in the care of patients with common variable immunodeficiency (CVID). The increasing pathogenic knowledge and potential therapeutic implications require a new evaluation of the status quo. Recent findings: The conundrum of the simultaneous manifestation of primary immunodeficiency and autoimmune disease (AID) is increasingly elucidated by newly discovered genetic defects. Thus, cytotoxic T lymphocyte-associated antigen 4 or caspase-9 deficiency presenting with CVID-like phenotypes reiterate concepts of immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome and autoimmune lymphoproliferative syndrome. Activating signaling defects downstream of antigen or cytokine receptors are often associated with loss-of-tolerance in the affected patients. Increasingly, forms of combined immunodeficiency are discovered among CVID-like patients. Although different autoimmune manifestations often coincide in the same patient their immunopathology varies. Treatment of AID in CVID remains a challenge, but based on a better definition of the immunopathology first attempts of targeted treatment have been made. Summary: The increasing comprehension of immunological concepts promoting AID in CVID will allow better and in some cases possibly even targeted treatment. A genetic diagnosis therefore becomes important information in this group of patients, especially in light of the fact that some patients might require hematopoietic stem cell transplantation because of their underlying immunodeficiency.